Features of Qualification and Prevention of Smuggling of Narcotic Drugs, Psychotropic Substances: their Precursors or Analogues - Gazinurovna, Khayrullina Rezeda; Dmitrievna, Kravchenko Olga; Valerievna, Tobolskaya Victoria; Yuryevna, Nedorezova Olga (Cuestiones Políticas, 2020)
The article is dedicated to the consideration of factors influencing the state of the situation in Russia in the field of detection and repression of the smuggling of narcotic drugs, psychotropic substances, their precursors, and analogues. In the methodological field it is an analytical research based on documentary, close to legal hermeneutics. Specifically, thearticle analyses Russian legislation, offers options to solve problems in the field of smuggling narcotic drugs, psychotropic substances, their precursors, and analogues. The authors consider the real problems of countering the drug threat, which is currently a serious obstacle to the development of the state.  By way of concluding the nature and magnitude of the negative consequences, illicit trafficking in narcotic drugs, psychotropic substances, their precursors, and analogues can be classified as direct threats to national security. Today, the issues of countering the illegal circulation of narcotic drugs, using modern information technologies, improving mechanisms to convert goods obtained from illicit drug trafficking into state revenue are relevant.